Review of the genera Homotropus Förster and Syrphoctonus Förster (Hymenoptera, Ichneumonidae, Diplazontinae) from Japan - Morishita, Shunsuke; Watanabe, Kyohei (Zootaxa, 2025)
The Japanese species of the genera Homotropus Förster and Syrphoctonus Förster are reviewed. Twelve species of the former and two species of the latter are recognised in the Japanese fauna. Homotropus japonicum sp. nov. is described as new. Homotropus areolaris (Uchida, 1957), H. crassicornis Thomson, 1890, H. klopfsteinae Johansson, 2020, H. megaspis Thomson, 1890, and H. sundevalli (Holmgren, 1858) are newly recorded from Japan. Generic positions of Syrphoctonus infuscatus Uchida, 1957 and S. kuroashii Uchida, 1957 are changed from Syrphoctonus to Homotropus. The following four synonyms are newly proposed: S. momoii Uchida, 1957 = H. megaspis; S. spinosus Uchida, 1957 = H. areolaris (Uchida, 1957); S. enizemopsis Uchida, 1957 = H. sundevalli; S. tenuitibialis Uchida, 1957 = H. megaspis. Some new distribution records and a key to the Japanese species of Homotropus are also provided.